2020
DOI: 10.3389/fmicb.2020.00702
|View full text |Cite
|
Sign up to set email alerts
|

Acute Plasmodium berghei Mouse Infection Elicits Perturbed Erythropoiesis With Features That Overlap With Anemia of Chronic Disease

Abstract: Severe malaria anemia is one of the most common causes of morbidity and mortality arising from infection with Plasmodium falciparum. The pathogenesis of malarial anemia is complex, involving both parasite and host factors. As mouse models of malaria also develop anemia, they can provide a useful resource to study the impact of Plasmodium infections and the resulting host innate immune response on erythropoiesis. In this study, we have characterized the bone marrow and splenic responses of the erythroid as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 80 publications
4
9
0
Order By: Relevance
“…The changes in parasitaemia induced by the inoculation of P. berghei are consistent with the results of previous investigators [ 31 , 32 ]. As presented in Table 2 and Additional file 1 : Figure S1, evident increases ( p < 0.05) in percentage parasitaemia in control (untreated inoculated mice) were noticed on day 4 (14.40 ± 0.45) and day 5 (16.37 ± 1.25) post-inoculation compared with 9.40 ± 1.23 for day 3.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The changes in parasitaemia induced by the inoculation of P. berghei are consistent with the results of previous investigators [ 31 , 32 ]. As presented in Table 2 and Additional file 1 : Figure S1, evident increases ( p < 0.05) in percentage parasitaemia in control (untreated inoculated mice) were noticed on day 4 (14.40 ± 0.45) and day 5 (16.37 ± 1.25) post-inoculation compared with 9.40 ± 1.23 for day 3.…”
Section: Resultssupporting
confidence: 92%
“…Changes in the haematological profile are a consistent feature in malaria parasitaemia and represent a basic malaria infection pattern. In the control group, the observed decrease in blood parameters corroborates with previous reports documenting haematological indices of malaria-infected patients [34,35] and increased RBCs breakdowns in P. berghei-infected mice, thus resulting in anaemia [32]. In marked contrast to the control, amounts of WBC, RBC, Hb and PCV in PHCSBD-treated groups were significantly (p < 0.05) higher (Table 4).…”
Section: Resultssupporting
confidence: 89%
“…Inflammation from severe tissue damage or infection (e.g. bacterial or parasitic) can impede the erythropoietin (EPO) response in bone marrow, suppressing erythroid progenitor cells (EPCs) and increasing EPCs in the peripheral blood after severe injury 1,2 ; however, splenic erythropoiesis is initiated to produce new erythrocytes to compensate for the anemia. Similarly, tissue hypoxia resulting from disease and injury, 3,4 high altitude (hypobaric hypoxia (HB)) exposure, 5 or severe hemorrhage (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In separate studies, [16,17] associated diminution in body weight to the loss of appetite, reduced metabolism, altered gut function, hypoglycemia and most importantly massive destruction of erythrocytes. In addition, P. berghei infected rats (19) and L .donovani infected mice (20) studies reported high anemia which was due to the destruction of erythrocytes and splenocytes respectively.…”
Section: Discussionmentioning
confidence: 99%